Pathogenic potential and antimicrobial resistance of Staphylococcus pseudintermedius isolated from human and animals - Glajzner, Paulina; Szewczyk, Eligia M; Szemraj, Magdalena (Folia microbiologica, 2023)
Crossing of interspecies barriers by microorganisms is observed. In recent years, Staphylococcus pseudintermedius-a species formerly thought to be animal-has also been isolated from human clinical materials. Many virulence factors are responsible for the colonization, which is the first step an infection, of the new host organism. We analyzed the factors influencing this colonization as well as susceptibility to antibiotics in fourteen S. pseudintermedius strains isolated from clinical cases from humans and animals. The occurrence of genes responsible for binding elastin, fibronectin, and fibrinogen and some phenotypic features, although different between strains, is comparable in both groups. However, the animal isolates had more genes coding for virulence factors. All isolates tested had the exfoliating toxin gene and the leukotoxin determining genes, but only the human strains had enterotoxin genes. The assessment of antibiotic resistance of strains of both groups indicates their broad resistance to antibiotics commonly used in veterinary medicine. Antibiotic resistance was more common among animal isolates. The multilocus sequence typing analysis of the studied strains was performed. The results indicated a large diversity of the S. pseudintermedius population in both studied groups of strains. Equipped with important virulence factors, they showed the ability to infect animals and humans. The clonal differentiation of the methicillin-susceptible strains and the multidrug resistance of the strains of both studied groups should be emphasized. The considerable genetic diversity of strains from a limited geographical area indicates the processes of change taking place within this species. Thus, careful observation of the ongoing process of variation is necessary, as they may lead to the selection of S. pseudintermedius, which will pose a significant threat to humans.
Keywords: stafylokokové infekce; Staphylococcal infections; Virulence Factors; Bacterial adhesions; Drug Resistance, Bacterial; antibakteriální látky; Zoonotic infections; Microbial Sensitivity Tests; Methicillin resistance; Staphylococcus; faktory virulence; Animals; lidé; Anti-Bacterial Agents; Humans; bakteriální léková rezistence; zvířata; mikrobiální testy citlivosti; Staphylococcal Infections